Le forme della censura religiosa nell’Egitto moderno. Il caso Awlād Hāratinā di Nağīb Mahfūz - Danilo Marino (Between, 2012)
In this paper I will focus on the censure applied by religious authorities, who intervene in tracing the limits between the licit and illegal when an author employ the religious stories as literary materials. I will trace the complex editorial story of Awlād Ḥāratinā a novel of Nağīb Maḥfūẓ (1911-2006). When it was published in 1959 on the cairene newspaper Al-Ahrām, numerous protesters asked for an interruption of publishing and to ban the novel for its blasphemous contents. Even if the printing of the work could be completed, Awlād Ḥāratinā was never published as a book in Egypt, only in 1967 the libanaise Dār al-Ᾱdāb issued the novel but it was forbidden in Egypt.The Islamic censure judged  Awlād Ḥāratinā a work that deride religion for its non orthodox use of the sacred story. Not only the structure of the book, but the stories of its characters seemed to be more closer to prophetic lives. In fact, the narration represents the sacred story of the humanity in a usual modern cairen neighborhood, that is to say employing imagination where devotion, authenticity and respect were required. Maḥfūẓ’s explanations of a political rather than a religious interpretation was useless. Through the analysis of original documents, I intend to deal with the nature of this ban, because the censure wasn’t a formal political or religious interdict, nor it was an official juridical decision, but it seemed more a informal forbid or a kind of auto-censure influenced by the pressures put on by the context. In 1988 two events renewed the attention on Awlād Ḥāratinā: Nağīb Maḥfūẓ was aworded the Nobel prize for literature and Salma Rushdie published The satanic Verses, that was followed by the death sentence (fatwā’) cursed by Khomeiny. Thus, the similarities between the two works soon arose and some Islamists started to attack Maḥfūẓ. As a result of that tension, in 1994 some fanatics  attempted on Maḥfūẓ’s life. In this paper I will trace a comparison between Awlād Ḥāratinā and The Satanic Verses affairs and I will deal with Maḥfūẓ’s ambiguous positions toward Rushdie’s death sentence, discussing his numerous statements on the boycott of The Satanic Verses to prevent a social and religious conflict.